The Uniqueness of Analytic Functions on Annuli Sharing Some Values - Hong-Yan Xu; Zu-Xing Xuan (Abstract and Applied Analysis, 2012)
The purpose of this paper is to deal with the shared values and uniqueness of analytic functions on annulus. Two theorems about analytic functions on annulus sharing four distinct values are obtained, and these theorems are improvement of the results given by Cao and Yi.